Self-evaluation of prospective special educators’ competencies from the standpoint of personalised learning paradigm - Ališauskienė, Stefanija; Kaffemanienė, Irena; Ališauskas, Algirdas (Special Education, 2016)
The article analyses how self-evaluation of prospective special educators’ acquired competencies helps them to identify their needs and study expectations from the standpoint of personalised learning and opens up ways for teachers to start a dialogue with students, better understand learners and, considering their professional interests, improve study quality. The study was aimed to disclose theoretical links between personalised learning and students’ active participation in the study process, to determine how future special educators self-evaluate acquired competencies and disclose their learning interests, interpret self-evaluation results of prospective special educators’ competencies, based on the theoretical methodological model of personalised learning. Seeking the research aim, mixed methodology was employed: quantitative and qualitative research and data processing methods were combined. The study was attended by 78 I-IV year students of the first study cycle of special education. The study demonstrated that personal and social competencies were an integral part of professional competencies; therefore, in students’ opinion, these competencies should be given particularly much attention educating future special educators. Prospective special educators emphasise the influence of studies on changes in and maturity of their values, self-awareness, personal changes. Less expressed characteristics of personalised learning are self-directed learning, implementation of experiential abilities and purposefulness.
Keywords: prospective special educators; self-evaluation of competencies; personalised learning